Cardiorespiratory Fitness, Adiposity, and Cardiometabolic Risk Factors in Schoolchildren: The FUPRECOL Study (2017)
The aim of this study was to investigate the association between cardiorespiratory fitness (CRF) and cardiovascular risk factors (CVRF) in schoolchildren. A secondary aim was to evaluate the degree of association between overall and abdominal adiposity and CRF in a total of 1,875 children and adolescents attending public schools. We expressed CRF performance as the nearest stage (minute) completed and the estimated peak oxygen consumption. A CVRF (Z score) was calculated and participants were divided into tertiles according to low and high levels of overall (sum of the skinfold thicknesses) and abdominal adiposity. Schoolchildren with a high-level of overall adiposity demonstrated significant differences in seven of the 10 variables analyzed (i.e., systolic and diastolic blood pressure, triglycerides, triglycerides/high density lipoproteins [HDL-c] ratio, total cholesterol, glucose, C-reactive protein [usCRP], HDL-c, low density lipoproteins [LDL-c], and cardiovascular risk score). Schoolchildren with high levels of both overall and abdominal adiposity and low CRF had the least favorable CVRF score. © 2016, © The Author(s) 2016.